Mental disorders and employment status in the São Paulo Metropolitan Area, Brazil: gender differences and use of health services - Mariane Henriques França; Sandhi Maria Barreto; Flavia Garcia Pereira; Laura Helena Silveira Guerra de Andrade; Maria Cristina Alochio de Paiva; Maria Carmen Viana (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2017)
Abstract: Mental disorders are associated with employment status as significant predictors and as consequences of unemployment and early retirement. This study describes the estimates and associations of 12-month DSM-IV prevalence rates of mental disorders and use of health services with employment status by gender in the São Paulo Metropolitan Area, Brazil. Data from the São Paulo Megacity Mental Health Survey was analyzed (n = 5,037). This is a population-based study assessing the prevalence and determinants of mental disorders among adults, using the Composite International Diagnostic Interview. The associations were estimated by odds ratios obtained through binomial and multinomial logistic regression. This study demonstrates that having mental disorders, especially mood disorders, is associated with being inactive or unemployed among men and inactive among women, but only having a substance use disorder is associated with being unemployed among women. Among those with mental disorders, seeking health care services is less frequent within unemployed.